Comparison of the predictive effects of individual and social factors on substance abuse severity - Şen, Selçuk; Sapancı, Ahmet (Journal of Dependence, 2024)
Objective: The aim of this study is to investigate the impact of individual and social factors in preventing substance dependency, with a focus on identifying protective factors in this process. The assessment is particularly directed towards determining which factors are more effective.Method: A total of 101 male participants aged 18-65 were included in the research. Surveys such as "Personal Sociodemographic Information Form," "Family Protective Factors Scale," "Multidimensional Perceived Social Support Scale," "Brief Resilience Scale," "Coping Styles Scale Short Form," "Short Self-Control Scale," "Addiction Profile Index Short Form," and "Emotion Regulation Scale" were administered.Results: Perceived social support, impulsivity, focusing and expressing emotions were identified as protective factors that best explain the severity of addiction. Additionally, it was found that social protective factors have a higher explanatory power for substance addiction compared to individual protective factors.Conclusion: When developing strategies to combat substance abuse, it may be effective to focus on strengthening individuals' social support systems, increasing their emotional regulation skills and reducing impulsivity. Furthermore, the results of this study emphasize the importance of a broad perspective in combating addiction and suggest that further research is needed to understand the interactions between individual and social factors.
Keywords: Substance abuse; individual factors; social factors; perceived social support; coping styles